Mirror‐Image Cofacial Coronene Dimers Characterized by CD and CPL Spectroscopy: A Twisted Bilayer Nanographene. Issue 11 (29th October 2021) - Uehara, Keiji; Kano, Haruka; Matsuo, Kyohei; Hayashi, Hironobu; Fujiki, Michiya; Yamada, Hiroko; Aratani, Naoki
Abstract: The front cover artwork is provided by Naoki Aratani, Hiroko Yamada, and co‐workers at NAIST (Japan). This picture shows Mt. Fuji, the highest mountain in Japan, reflecting off the water surface in a beautiful symmetrical form. On this image, we superimposed the mirror‐image CPL spectra obtained in this study for a 1, 8‐naphthylene‐linked face‐to‐face coronene dimer. Read the full text of the Communication at 10.1002/cptc.202100166 . Abstract : "Bilayer graphene (BLG), which changes its electronic properties significantly depending on the interplanar distance and rotation angle, is a hot research topic. Although BLG has excellent electronic and optical properties compared with existing materials, the BLGs obtained by the top‐down method have various types of defects. Herein, we report the bottom‐up construction of a 1, 8‐naphthylene linked face‐to‐face coronene dimer and its unique (chir)optical characteristics as a molecular‐scale BLG model compound…" This and more about the story behind the front cover can be found in the Communication at 10.1002/cptc.202100166 .